REVIEW OF RISK MANAGEMENT IN RENT TO OWN (RTO) SCHEME IN MALAYSIA - Pei Nei, Penny Goh; Mohd Tobi, Siti Uzairiah; Jasimin, Tuti Haryati (PLANNING MALAYSIA, 2023)
This paper focuses on the review of risk management in Rent to Own (RTO) scheme in Malaysia. The objectives are to review the risk management factors in RTO scheme and the strategies to overcome the risk. This study employs a desktop study by collecting the research papers and data in the online databases. RTO Scheme is a concept that employs the rental market like Private Rented Sector (PRS) in the properties that allows ownership after the tenancy period has been expired. The RTO scheme is a type of financial schemes that allows property leasing for between twelve (12) months to five (5) years and ownership upon the maturity of the leasing period. This is an initiative by the Economic Planning Unit (EPU) and the Ministry of Housing and Local Government (MHLG) to implementing the National Housing Policy 2018-2025. The RTO scheme is for home buyers to have financial planning to rent before they buy. The calculation of the mortgage loan for RTO Scheme is based on the rental income and the rental deposit. Additionally, preliminary case study has been conducted to the RTO schemes through onsite and interview with the Developer. The results are to review the risk factors in the RTO Scheme and the marketing strategies. The outcomes of the research are to give input to the house buyers to be confident to buy houses under the RTO Scheme.